2019
DOI: 10.18203/2349-2902.isj20192957
|View full text |Cite
|
Sign up to set email alerts
|

Proximal fibular osteotomy for pain relief and functional improvement in patients of osteoarthritis of knee

Abstract: Background: The aim of this study was to evaluate the effect of proximal fibular osteotomy in relieving pain and functional improvement in patients of osteoarthritis knee.Methods: We selected 38 patients with KOA, out of which 30 patients gave written informed consent and underwent proximal fibular osteotomy. The median time of follow-up was 13.3 months. Preoperative and postoperative weight-bearing and whole lower extremity radiographs were obtained to analyse the alignment of the lower extremity (tibio-femor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 7 publications
(8 reference statements)
4
24
1
Order By: Relevance
“…The results of their study suggest that the benefits of PFO may not be long-lasting. This is in contrast with the improved radiological outcome reported in the present study and several other published studies [7,9,[12][13][14][15]. A retrospective study by Yang et al has shown that the improvement in radiological outcome continues beyond one year [15].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of their study suggest that the benefits of PFO may not be long-lasting. This is in contrast with the improved radiological outcome reported in the present study and several other published studies [7,9,[12][13][14][15]. A retrospective study by Yang et al has shown that the improvement in radiological outcome continues beyond one year [15].…”
Section: Discussioncontrasting
confidence: 99%
“…The AKSS grades the outcome as poor (<60), fair (60-69), good (70-79), and excellent (>80) [18]. An excellent outcome in functional subsets of the AKSS (72.06 ±7.30 and 87.90 ±7.08) has been reported in another study [9]. However, that study involved patients who had comparatively higher preoperative clinical and functional scores (62.13 ±11.90 and 55.16 ±4.15) compared to our study (56.49 ±6.95 and 48.24 ±14.31) and that might be the reason for the higher postoperative scores.…”
Section: Discussionmentioning
confidence: 66%
“…The incidence of knee OA increases with age and increases with longevity and higher mortality. [7][8][9] In the current study, the mean age of the patients was found to be 58.9 years. Fifty percent of patients were in the age groups of 56 to 65 years.…”
Section: Discussionmentioning
confidence: 79%
“…Additionally, obvious change in alignment was observed in the whole lower extremity radiographs in 24 out of 30 patients. In three patients tibio-femoral angle showed progressive more varus alignment after proximal fibulectomy [18] . PFO has emerged as a new surgery to relieve pain and improve joint function in patients with knee osteoarthritis.…”
Section: Discussionmentioning
confidence: 87%
“…walking) was also obviously improved when compared with the preoperative state. PFO also improved the axial alignment of the lower extremity in some patients, especially in those with severe genu varus [17,18] .…”
Section: Discussionmentioning
confidence: 89%